Study on hot deformation behaviour and processing maps of low carbon bainitic steel. (5th February 2015) - Yang, Zhinan; Zhang, Fucheng; Zheng, Chunlei; Zhang, Ming; Lv, Bo; Qu, Lin
Highlights: Constitutive model showed an r of 0.982 between tested and predicted stress. Flow localisation was found in the instability regions. Deformation mechanism in the stability regions is dominated by DRX. The optimum processing region were at 930–980 °C and 0.001–0.014 s −1 . Abstract: The hot deformation behaviour of low carbon bainitic steel, 29MnSiCrAlNiMo steel, was studied at a temperature range of 800–1100 °C and a strain rate range of 1 × 10 −2 to 1 × 10 1  s −1 . The flow curves display two features, with steady-state region and without it. After a comprehensive consideration of the deformation temperature, strain rate and strain, a constitutive model was proposed, exhibiting a correlation coefficient of 0.982 between the experimental and predicted stress values. The result shows a decreased deformation activation energy from 460 to 267 kJ/mol with increasing strain level from 0.1 to 0.8. Processing maps at different strain levels were also constructed, which exhibit an expanded instability region with increasing strain. Microstructural observations show that the flow localisation occurred when the hot working was performed on the instability regions, and partial dynamic recrystallisation occurred along the grain boundaries and deformation bands, resulting in a mischcrystal structure. The optimum hot working processing parameters for the studied steel are at 930–980 °C and 0.001–0.014 s −1, and a full dynamic recrystallisation structure with a fine and homogeneous grain can be obtained. Microstructure observation verifies the applicability of the processing maps for optimising the processing parameters of the 29MnSiCrAlNiMo steel.